Facile synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone - Upadhyay, Puspesh K.; Prasad, Rajendra; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2009)
A short synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone was achieved from L-serine employing Horner-Emmons olefination as the key step. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Horner-Emmons olefination; L-serine; Pyridone; Z-selectivity

Novel synthesis of coumarins employing triphenyl(alpha-carboxymethylene)-phosphorane imidazolide as a C-2 synthon - Upadhyay, Puspesh K.; Kumar, Pradeep (Tetrahedron Letters, 2009)
A novel one-pot synthesis of coumarins via intramolecular Wittig cyclization from the reaction of phenolic compounds containing ortho-carbonyl group and triphenyl(alpha-carboxy methylene)phosphorane imidazolide is described. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Carbonyldiimidazole; Coumarins; Intramolecular Wittig reaction; Phenolic compound; Phosphorane

Concise synthesis of (2S,3S,4S)-2-(Hydroxymethyl)pyrrolidine-3,4-diol (LAB1) - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
The synthesis of (2S,3S,4S)-2-(hydroxymethyl)pyrrolidine-3,4-diol (LAB1) from Garner's aldehyde is described using the Sharpless asymmetric dihydroxylation as the key step.
Keywords: alkaloid; azasugars; diastereoselectivity; Garner's aldehyde; pyrrolidine; Wittig reaction

Short and efficient synthesis of (S)-(+)-2-(Hydroxymethyl)-6-piperidin-2-one - Upadhyay, Puspesh K.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A concise synthesis of (S)-(+)-2-(hydroxymethyl)-6-piperidin-2-one is described that employs L-aspartic acid as chiral pool starting material and Wittig reaction as the key step.
Keywords: Amino acid; Hydrogenation; L-aspartic acid; pipecolate; piperidone; Wittig reaction

Asymmetric dihydroxylation route to (-)-bulgecinine - Show, Krishanu; Upadhyay, Puspesh K.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
The stereoselective synthesis of (-)-bulgecinine is reported from L-aspartic acid using Sharpless asymmetric dihydroxylation and intramolecular cyclization via nucleophilic displacement of alpha-tosylate as key steps. (C) 2011 Elsevier Ltd. All rights reserved.